ZnSe/ZnO Nano‐Heterostructures for Enhanced Solar Light Hydrogen Generation. Issue 28 (9th October 2017) - Shaikh, Asiya F.; Arbuj, Sudhir S.; Tamboli, Mohaseen S.; Naik, Sonali D.; Rane, Sunit B.; Kale, Bharat B.
Abstract: The one dimensional Zinc Selenide/Zinc Oxide (ZnSe/ZnO) nano‐heterostructures were prepared using solvo/hydrothermal reaction technique with varying concentration of ZnSe. The prepared nano‐heterostructures were characterized with various techniques. X‐ Ray Diffraction (XRD) indicates the formation of cubic ZnSe and hexagonal phase of ZnO. Field Emission Scanning Electron Microscopy (FESEM) depicts the formation of rod shaped ZnO nanostructures decorated with spherical nanoparticles of ZnSe. Field Emission Transmission Electron Microscopy (FETEM) validates the formation ZnO nanorods of size 30–40 nm along with spherical ZnSe (25‐30 nm) nanostructures. The UV‐Visible absorption spectra analysis clearly depicts the extended absorbance in the visible region. Photoluminescence study indicates the sharp band edge emission peak at 390 nm and broad peak at 475 nm. With further increase in ZnSe concentration, the intensity of band edge emission peak decreases due to the vacancy defects. The photocatalytic performance of prepared ZnSe/ZnO nano‐heterostructure was evaluated by studying the hydrogen (H2 ) generation via water (H2 O) splitting under UV‐Visible light. The ZnSe/ZnO (10:90 weight ratio) shows 491 μmol of H2 generation after 4 hours irradiation. With increase in amount of ZnSe upto 10 mol%, the H2 evolution was also enhanced due to narrowing of the band gap and suppression of recombination rate of charge carriers. Abstract : The ZnSe/ZnO nano‐heterostructures were successfully synthesized by solvo/hydrothermal method with varying concentration of ZnSe. The prepared nano‐heterostructures were characterized with various techniques. The photocatalytic performance of prepared ZnSe/ZnO nano‐heterostructure was evaluated by studying the hydrogen (H2 ) generation via water (H2 O) splitting under UV‐Visible light. The ZnSe/ZnO (10:90 weight ratio) shows 491 μmol of H2 generation after 4 hours irradiation.